Razvoj vojaške formacije in vojaškega delovanja Slovenskega domobranstva - Peter Papler; Darko Ščavničar; Tomaž Kladnik (Dileme)
Based on studying archival materials and literature, the article discusses the forming and development of the military formation and military operations of the Slovenian Home Guard. He notes that with the development of the political and military situation in the Province of Ljubljana, the Slovenian Home Guard quickly changed its composition and military operations. From defensive–policing formations stationed at military posts, the units evolved into mainly offensive military formations of quick-moving shock battalions. Autonomous military operations of SlovenianHome Guard units against Partisan units were hindered due to oversight by German police and, later, military commanders.